文化空缺与翻译 ：以《后宫甄嬛传》为例 = Cultural vacancy and translation : a study on the translation of empresses in the palace - 许瑞芳 Khaw, Vivian Rui Fang (2017)
语言是文化的承载体，因此翻译不仅是语言的转换，更是一种“跨文化交际”。自近代以来，文化翻译成为翻译界热切关注的议题之一。然而，不同语言所承载的文化大不相同，因此在两种语言之间存在着巨大的文化差异，文化空缺的现象即是文化差异所导致的其中一个问题，阻碍有效的文化交流并且对翻译带来了相当的困难。文化空缺现象具体如何产生，有何特征，是近年来学者的兴趣研究方向。如何处理中英文化中的文化空缺，采用适当的翻译策略是翻译的重要任务。本文结合翻译中文化空缺现象与中国古装电视剧《后宫甄嬛传》的美国版 Empresses in the Palace 来研究中英翻译过程中的文化差异与空缺。Empresses in the Palace 作为第一部正式进军美国市场的中国电视剧，在字幕翻译上遭受到许多批评。其翻译问题的产生主要能归咎于中英文化差异的不当处理。本文主要以文化空缺现象的角度探讨《甄嬛传》在中译英过程中的困难，并且提供克服空缺现象的翻译策略。As there exists a close relationship between language and culture, translation, first seemingly an inter-lingual activity, is in reality closely related to culture. Translators have taken an avid interest in the translation of culture in the last few decades. However, the diversity in language reflected a diversity in culture at the same time, and thus a huge difference between any two languages prevail. Vacancy is a translation phenomenon arising from the differences in culture. It hinders effective cross-cultural communication and is a problem not to be overlooked in translation. Since the discovery of cultural vacancy, it has been a point of interest for translation theorists. Translators have to approach this phenomenon with careful consideration and find ways to overcome this problem with suitable translation methods. The author of this paper aims to discuss this particular translation phenomenon, using a popular Chinese historical drama The Legend of Zhen Huan, also known as Empresses in the Palace, as an example to evaluate on the differences in the English and Chinese culture. This paper points out the translation problems and errors found in the US version of the drama and attempts to account for these problems using translation theories, with the focus being on the presence of cultural vacancy. This paper will also provide some strategies to overcome the problems posed by cultural vacancy.